Effect of Cognitive Behavioral Therapy on Functional Outcome in Patients with Lumbosacral Radiculopathy - Samir M. Fayez, Eman; Ahmed Elkashif, Shimaa; Fathi Sheir, Shereen; Sheir, Fathi; Gamal El-Din, Ayat; Salem, Shymaa; S. Mohamed, Shereen (Journal of Neonatal Surgery, 2025)
Background: Pain, tingling, numbness, or weakness that radiates down the lower back and into the lower extremities is known as lumbosacral radiculopathy. It is the most persistent type of musculoskeletal pain, marked by ongoing changes in the central nervous system. Eighty percent of people will experience it at any time throughout their lives. Objective: To examine the effectiveness of cognitive behavioral therapy (CBT) on functional outcomes in patients with lumbosacral radiculopathy. Subjects and Methods: Fifty-two patients with lumbosacral radiculopathy, with ages between 30 and 45 years, were selected from the Mataria Teaching Hospital clinic, and were randomly split into two groups with the same numbers; study group (GA) underwent cognitive behavioral therapy (CBT), and control group (GB) underwent selected physiotherapy training. Treatment was done two sessions/week for two months. All variables were evaluated before and after the intervention. Visual analogue scale (VAS), Oswestry disability index (ODI), and the fear-avoidance beliefs questionnaire (FABQ) were utilized to evaluate pain level, functional disability, and the effect of fear-avoidance beliefs linked to work and physical activity, respectively. An electro-goniometer was used for measuring active hip joint flexion. Stabilizer pressure biofeedback was applied to evaluate lumbar stability. Results: A significant drop in the VAS and ODI was observed in both groups after treatment in comparison to baseline (p < 0.05), with a more favorable effect observed in the GA. A significant increase in both lumbar stability and hip flexion angle was observed in the two groups after treatment in comparison to baseline (p < 0.05), with a more favorable effect observed in GA. Conclusions: CBT is a beneficial approach for alleviating pain and functional impairment in patients with lumbar radiculopathy.